2019
DOI: 10.1136/rapm-2018-000022
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy and impact of caudal block on surgical complications of hypospadias repair: a systematic review and meta-analysis

Abstract: Background and objectivesis commonly used for children undergoing hypospadias repair. However, the safety of caudal block for hypospadias repair in children is controversial in terms of surgical complications such as urethrocutaneous fistula and glans dehiscence. We sought to perform a meta-analysis to estimate the analgesic efficacy and relative complications of caudal block for hypospadias repair in children.MethodsWe identified comparative studies of caudal block versus peripheral nerve block or no caudal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Thank you for the opportunity to respond to Dr Haydar’s1 letter. We appreciated that Dr Haydar and his coauthors found our paper2 of interest. He brought up several points, which we agree are worth clarifying.…”
mentioning
confidence: 88%
“…Thank you for the opportunity to respond to Dr Haydar’s1 letter. We appreciated that Dr Haydar and his coauthors found our paper2 of interest. He brought up several points, which we agree are worth clarifying.…”
mentioning
confidence: 88%
“…We appreciated that Dr Niu and his co-authors found our paper1 2 of interest. He brought up several points, which we agree are worth clarifying.…”
mentioning
confidence: 88%
“…We read with interest the meta-analysis of caudal block for hypospadias repair by Zhu and colleagues 1. Their work helps to improve understanding about the relative efficacy of different analgesic techniques, but unfortunately perpetuates a baseless myth and overlooks important deficiencies in the works they cite regarding surgical complications.…”
mentioning
confidence: 99%